The Influence of Participative Leadership Style, Physical Work Environment and Work Discipline on the Performance of Employees at the Kramat Jati Religious Affairs Office, East Jakarta - Syarifa Aulia; Ahmad Cik; Kumba Digdowiseiso (Politeknik Siber Cerdika Internasional, 2024)
The purpose of this research is to determine the influence of a participative leadership style, physical work environment, and work discipline on the positive influence on the performance of employees at the Kramat Jati Religious Affairs Office, East Jakarta. The technique for taking this sample is saturated sampling, by taking the entire sample of 40 respondents. Data management uses descriptive methods and inferential statistical methods. The type of data used is primary data, namely data taken through questionnaires given to respondents. The data collection technique uses a questionnaire, namely by providing statements to parties related to the problem to be studied. Based on data management using descriptive analysis, the results of the regression equation are as follows Y = 0.740 + 0.416X1 + 0.208X2 +0.354X3. Testing the statistical model with the F test obtained an Fcount value of 54.092 with a sig value of 0.000, which means that participative leadership style, physical work environment and work discipline together have a positive effect on employee performance, while the t test obtained a participative leadership style of 3.290, physical work environment amounting to 2,216 and work discipline amounting to 2,254. with a sig value of 0.002 for participative leadership style, a sig value of 0.033 for physical work environment, and a sig value of 0.030 for work discipline, which means that participative leadership style, physical work environment and work discipline partially have a positive and significant effect on employee performance.